PENGARUH PENGGUNAAN SUPLEMEN BELAJAR AR SINAPS TERHADAP PEMAHAMAN KONSEP SISTEM PERNAPASAN SISWA SMA - Rini, Daniar Setyo; Azrai, Eka Putri; Inayah, Shabrina Syifa (Universitas Negeri Jakarta, 2024)
There are many levels of objects studied in biology, and parts of the anatomy and physiology of the body still need to be appropriately understood. This problem needs to be clarified to enhance students' understanding of concepts in studying biology, especially in the respiratory system topic. This study aims to determine the effect of Augmented Reality-based learning supplements (AR SINAPS) on high school students' conceptual understanding of the respiratory system. This research was conducted in January-April 2023 at SMAN 38 Jakarta, Indonesia class XI MIPA. This study used a quantitative approach with quasi-experimental methods and pretest-posttest group experimental research designs. The sample was randomly selected using the simple random sampling technique of 62 students: 31 in the experimental class (using AR SINAPS) and 31 in the control class (using E-Module). Data were obtained using a conceptual understanding test instrument of 30 multiple-choice questions. Furthermore, the collected data were analyzed using descriptive analysis, and the enhancement in understanding the concept of the respiratory system was measured by the normality gain test (N-Gain). The N-Gain value for the experimental class was higher than the control class; the experimental class was 0.69, and the control class was 0.55. The results of the N-Gain percentage of both classes were in the medium category with different categories of effectiveness; the experimental class was quite effective, and the control class was less effective. Based on the study's results, the AR SINAPS learning supplement significantly affects high school students' conceptual understanding of the respiratory system.